Determinants of house dust, endotoxin, and β‐(1→3)‐D‐glucan in homes of Danish children. (12th September 2014) - Holst, G.; Høst, A.; Doekes, G.; Meyer, H. W.; Madsen, A. M.; Sigsgaard, T.
Abstract: Little is known about the geographic variation and determinants of bacterial endotoxin and β ‐(1, 3)‐d ‐glucan in Danish house dust. In a population of 317 children, we: (i) described loads and concentrations of floor dust, endotoxin, and β ‐(1→3)‐d ‐glucan and (ii) their correlations and (iii) assessed their determinants; (iv) Finally, we compared our findings with previous European studies. Bedroom floor dust was analyzed for endotoxin content by the kinetic limulus amoebocyte lysate assay and for β ‐(1→3)‐d ‐glucan by the inhibition enzyme immunoassay. The parents answered questions regarding potential determinants. We found: geometric means (geometric standard deviations) 186 mg/m 2 (4.3) for dust; 5.46 × 10 3 EU/m 2 (8.0) and 31.1 × 10 3 EU/g (2.6) for endotoxin; and 142  μ g/m 2 (14.3) and 0.71 × 10 3   μ g/g (7.3) for β ‐(1→3)‐d ‐glucan. High correlations ( r  >   0.75) were found between floor dust and endotoxin and β ‐(1→3)‐d ‐glucan loads, while endotoxin and β ‐(1→3)‐d ‐glucan concentrations were moderately correlated ( r  =   0.36–0.41) with the dust load. Having a carpet was positively associated with dust load and with endotoxin and β ‐(1→3)‐d ‐glucan concentrations. Pet keeping, dwelling type, and dwelling location were determinants of endotoxin concentrations. No other determinants were associated with β ‐(1→3)‐d ‐glucan concentrations. Compared with other European studies, we found lower β ‐(1→3)‐d ‐glucan loads and concentrations but higher endotoxin loads and concentrations suggesting a geographically determined different composition of Danish floor dust compared with other European regions.